2018
DOI: 10.1111/birt.12379
|View full text |Cite
|
Sign up to set email alerts
|

Needs of parents and professionals to improve shared decision‐making in interprofessional maternity care practice: A qualitative study

Abstract: Parents and professionals will benefit from an intervention designed to improve SDM. A practical e-learning for all maternity care providers and e-health information for parents seems most appropriate. Key elements for the e-learning are raising awareness of the roles and responsibilities of parents and professionals, developing good communication skills and encouraging interprofessional collaboration. This requires a variety of educational strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
4
37
0
Order By: Relevance
“…It has been found that such requests can also create difficult situations for clinicians who may find it difficult to refuse a woman's requests for postterm IOL. Our findings pointed to the lack of information given to women, which aligns with studies of IOL information leaflets showing that pregnant women (even within the same country) received very different, sometimes even contradictory, information about IOL 51,52 and that decision aids 29,52,53 and/or shared decision-making interventions 54 are required. Our findings show that room for such an adjustment was not always provided and indicate that induced women may need supported opportunities to re-evaluate their hopes and expectations for the labor process, for example, the opportunity to review their birth plans in collaboration with their clinicians.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It has been found that such requests can also create difficult situations for clinicians who may find it difficult to refuse a woman's requests for postterm IOL. Our findings pointed to the lack of information given to women, which aligns with studies of IOL information leaflets showing that pregnant women (even within the same country) received very different, sometimes even contradictory, information about IOL 51,52 and that decision aids 29,52,53 and/or shared decision-making interventions 54 are required. Our findings show that room for such an adjustment was not always provided and indicate that induced women may need supported opportunities to re-evaluate their hopes and expectations for the labor process, for example, the opportunity to review their birth plans in collaboration with their clinicians.…”
Section: Discussionsupporting
confidence: 82%
“…49,50 This nuanced information and time to reflect on it is particularly important because the bias toward IOL acceptance is very strong. Our findings pointed to the lack of information given to women, which aligns with studies of IOL information leaflets showing that pregnant women (even within the same country) received very different, sometimes even contradictory, information about IOL 51,52 and that decision aids 29,52,53 and/or shared decision-making interventions 54 are required.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…8,23,24 Little is known about maternity care practitioners' attitudes about doulas and whether they view doulas as interprofessional team members. 8,23,24 Little is known about maternity care practitioners' attitudes about doulas and whether they view doulas as interprofessional team members.…”
mentioning
confidence: 99%
“…Interprofessional care teams reduce clinical errors, improve outcomes, and enhance patient satisfaction on labor and delivery floors. 8,23,24 Little is known about maternity care practitioners' attitudes about doulas and whether they view doulas as interprofessional team members. Conflict between doulas and maternity care practitioners has been documented, especially around medical decision-making.…”
mentioning
confidence: 99%